The Effect of Documentary Short Film on Enhancing Student's Confidence and Willingness to Perform CPR in Rural Areas - Yunita Wulansari; Guruh Wirasakti; Eky Madyaning Nastiti; Rida Darotin; Feri Ekaprasetia (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction: Out-of-hospital cardiac arrest (OHCA) is a critical emergency condition that necessitates immediate intervention to prevent fatal outcomes. In rural areas, where access to quality educational resources is limited, Documentary Short Films (DSF) can provide essential training that enhances individuals' confidence and willingness to act decisively in emergency situations involving OHCA through CPR. Objectives: To analyze the effect of DSF on enhancing student's confidence and willingness to perform CPR in rural areas. Methods: This study employed a quasi-experimental design utilizing a one-group pretest-posttest framework, conducted at a junior high school in Jember Regency, involving 72 students selected through proportionate stratified random sampling. The educational media utilized was a Documentary Short Film (DSF). Following the administration of a pretest questionnaire and the viewing of the DSF, a post-test was administered one week later to assess changes in self-confidence and willingness to perform CPR. Results The results indicate a significant difference in students' confidence and willingness to perform CPR before and after the educational intervention using the DSF (p < 0.05). The average self-confidence score among respondents rose from 5.78 (2 – 3 questions responding with 'confidence') to 9.43 (4 – 5 questions responding with 'confidence'). Additionally, the average willingness score showed an improvement from 9.13 (3 – 5 questions responding with 'willing') to 15.68 (7 – 8 questions responding with 'willing'). Conclusions: DSF for CPR training effectively enhances rural middle school students' confidence and willingness, improving community emergency response and safety .